Changing Interpretive Schemes and Organizational Restructuring: The Example of a Religious Order - Bartunek, Jean M. (Administrative Science Quarterly, 1984)
Jean M. Bartunek This paper reports a case study of a religious order whose shared interpretive schemes (the schemata that map its experience of the world), especially its understanding of its mission, were being substantially changed. During thistime the order underwent a major revision in structure. On the basis of the case, the paper explores ways interpretive schemes undergo fundamental change and ways these changes are linked to restructuring. The paper proposes that major changes in interpretive schemes occur through dialectical processes in which old and new ways of understanding interact, resulting in a synthesis. The process of change in interpretive schemes is in a reciprocal relationship with changes in structure. This relationship is not direct, but rather is mediated by the actions of organizational members and their emotional reactions to change. Environmental forces are likely to initiate the change, but the way the environment is interpreted by organizational members affects the type of change that takes place. Similarly, the way the organization's leadership initiates or responds to alternate interpretive schemes limits the type of change in understanding that can occur.